Is SARS-CoV-2 Vertically Transmitted? - Simões e Silva, Ana Cristina; Leal, Caio Ribeiro Vieira (Frontiers in Pediatrics, 2020)
At the end of 2019, in Wuhan (China), the onset of a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was observed. The disease, named COVID-19, has a wide spectrum of clinical presentations, ranging from asymptomatic or mild to critical, and for some patients the disease is even fatal. Apparently, being a child or being pregnant does not represent an additional risk for adverse outcomes. The purpose of this mini-review was to investigate what is in the scientific literature, so far, in regard to vertical transmission of SARS-CoV-2. Data were obtained independently by the two authors, who carried out a systematic search in the PubMed, Embase, LILACS, Cochrane, Scopus and SciELO databases using the Medical Subject Heading terms “coronavirus,” “COVID-19,” and “vertical transmission.” Few studies about the vertical transmission of SARS-CoV-2 are found in the literature. In all case reports and case series, the mothers' infection occurred in the third trimester of pregnancy, there were no maternal deaths, and most neonates had a favorable clinical course. The virus was not detected in the neonate nasopharyngeal swab samples at birth, in the placenta, in the umbilical cord, in the amniotic fluid, in the breast milk or in the maternal vaginal swab samples in any of these articles. Only three papers reported neonatal SARS-CoV-2 infection, but there is a bias that positive pharyngeal swab samples were collected at 36 h and on the 2nd, 4th, and 17th days of life. The possibility of intrauterine infection has been based mainly on the detection of IgM and IL-6 in the neonates' serum. In conclusion, to date, no convincing evidence has been found for vertical transmission of SARS-CoV-2.